2005
DOI: 10.1152/ajpheart.00483.2005
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of subclinical hypothyroidism reverses ischemia and prevents myocyte loss and progressive LV dysfunction in hamsters with dilated cardiomyopathy

Abstract: . Treatment of subclinical hypothyroidism reverses ischemia and prevents myocyte loss and progressive LV dysfunction in hamsters with dilated cardiomyopathy. Am J Physiol Heart Circ Physiol 289: H2409 -H2415, 2005. First published July 15, 2005; doi:10.1152/ajpheart.00483.2005.-Growing evidence suggests that thyroid dysfunction may contribute to progression of cardiac disease to heart failure. We investigated the effects of a therapeutic dose of thyroid hormones (TH) on cardiomyopathic (CM) hamsters from 4 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
42
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 39 publications
10
42
0
1
Order By: Relevance
“…The administration of replacement doses of L-T 4 reduces myocyte apoptosis and is able to improve cardiovascular performance and ventricular remodelling in experimental hypothyroidism (7,18,89,96). This is in line with the results of some randomized and placebo-controlled studies that demonstrated (74,75,79,97,98).…”
Section: Treatment Of Hf In Hypothyroid Patientssupporting
confidence: 78%
See 2 more Smart Citations
“…The administration of replacement doses of L-T 4 reduces myocyte apoptosis and is able to improve cardiovascular performance and ventricular remodelling in experimental hypothyroidism (7,18,89,96). This is in line with the results of some randomized and placebo-controlled studies that demonstrated (74,75,79,97,98).…”
Section: Treatment Of Hf In Hypothyroid Patientssupporting
confidence: 78%
“…The conversion of T 4 to T 3 is impaired and a low serum T 3 syndrome may develop in cardiac dysfunction (7,89,90,91,92). This condition is a strong predictor of mortality in patients with severe heart disease (7,89,90,91,92).…”
Section: Hf and Hypothyroidismmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that thyroid hormone treatment of patients and experimental animal models of heart failure can improve cardiac function has been attributed in part to its regulation of cardiac genes (1)(2)(3)(4)(5). It has also been well documented that thyroid hormones stimulate physiologic cardiac hypertrophy (6); however, the intracellular mechanisms underlying this response remain poorly defined.…”
mentioning
confidence: 99%
“…Recent published studies supporting the cytosolic localization and non-transcriptional activities of thyroid hormone receptors may underlie thyroid hormone-induced physiological growth (9 -11). Evidence of protein-protein interactions between cytosolic thyroid hormone receptors and the p85␣ regulatory subunit of phosphatidylinositol 3-kinase (PI3K), 2 and activation of PI3K activity by T3 treatment have been reported (12,13). Activation of the PI3K␣-Akt-mTOR pathway by IGF-1 and transgenic animal models expressing molecular components of this pathway have implicated the PI3K-Akt signaling pathway in determining heart size and physiologic cardiac growth (14 -18).…”
mentioning
confidence: 99%